2020
DOI: 10.31234/osf.io/8ynca
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Opposite effects of transcranial direct current stimulation (tDCS) on sustained attention in individuals with high and low levels of dispositional mindfulness

Abstract: Objective: Some studies suggest a link between mindfulness and attentional functioning. Using transcranial direct-current stimulation (tDCS), we tested the hypothesis that mindfulness might improve vigilance through enhanced prefrontal functioning. Methods: We compared the performance of individuals with low versus high dispositional mindfulness (LDM vs HDM) under anodal tDCS of the right prefrontal region and in a sham condition. Results: The stimulation improved vigilance performance in the LDM group and red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
1
0
0
Order By: Relevance
“…Alternatively, mindfulness disposition, which is often considered to be in anticorrelation with mind-wandering, might lend itself to an analogous interpretation (Seli et al, 2016). Interestingly, it was recently found that tDCS decreased performance in a sustained attention task only in participants with high and not low dispositional mindfulness (Molina et al, 2020). This finding fits well with the idea of different internal states whose degree of intentionality and control always reflect the LC-driven transitions between explorative and exploitative mental operations (Mittner et al, 2016).…”
Section: Discussionsupporting
confidence: 54%
“…Alternatively, mindfulness disposition, which is often considered to be in anticorrelation with mind-wandering, might lend itself to an analogous interpretation (Seli et al, 2016). Interestingly, it was recently found that tDCS decreased performance in a sustained attention task only in participants with high and not low dispositional mindfulness (Molina et al, 2020). This finding fits well with the idea of different internal states whose degree of intentionality and control always reflect the LC-driven transitions between explorative and exploitative mental operations (Mittner et al, 2016).…”
Section: Discussionsupporting
confidence: 54%